African-American crack abusers and drug treatment initiation: barriers and effects of a pretreatment intervention - Lam Wendy KK; Luseno Winnie K; Riehman Kara S; Zule William A; Wechsberg Wendee M (BMC, 2007)
Abstract Background Individual and sociocultural factors may pose significant barriers for drug abusers seeking treatment, particularly for African-American crack cocaine abusers. However, there is evidence that pretreatment interventions may reduce treatment initiation barriers. This study examined the effects of a pretreatment intervention designed to enhance treatment motivation, decrease crack use, and prepare crack abusers for treatment entry. Methods Using street outreach, 443 African-American crack users were recruited in North Carolina and randomly assigned to either the pretreatment intervention or control group. Results At 3-month follow-up, both groups significantly reduced their crack use but the intervention group participants were more likely to have initiated treatment. Conclusion The intervention helped motivate change but structural barriers to treatment remained keeping actual admissions low. Policy makers may be interested in these pretreatment sites as an alternative to treatment for short term outcomes.